Cultural adaptation of The End-Stage Renal Disease Adherence Questionnaire for hemodialysis patients - Silvia Maria de Sá Basilio Lins; Josete Luzia Leite; Simone de Godoy; Patrícia dos Santos Claro Fuly; Silvia Teresa Carvalho de Araújo; Ítalo Rodolfo Silva
ABSTRACT Objective: To describe the stages in the cultural adaptation of "The End-Stage Renal Disease Adherence Questionnaire" for use in Brazil. Method: A descriptive, transversal study with a quantitative approach. The cultural adaptation followed the steps of translation, professional committee, back translation, panel of patients and pretest. Results: the translation stage created a version in Portuguese that was analyzed by specialists, who suggested alterations in the title, seven sentences in the questions and three sets of answers. In the panel of patients phase, two questions were altered. The back translation considered the original characteristics of the instrument were maintained, likewise there were no modifications in the pretest phase. The third version written in Portuguese was considered to be the final version of the questionnaire. Conclusion: this instrument should facilitate nursing care management in hemodialysis, enabling the monitoring of adherence among these patients and also contribute to improving the indicators of morbidity and mortality.